2015
DOI: 10.1111/1556-4029.12887
|View full text |Cite
|
Sign up to set email alerts
|

Mining for Murder‐Suicide: An Approach to Identifying Cases of Murder‐Suicide in the National Violent Death Reporting System Restricted Access Database

Abstract: The National Violent Death Reporting System (NVDRS) is a United States Centers for Disease Control and Prevention (CDC) database of violent deaths from 2003 to the present. The NVDRS collects information from 32 states on several types of violent deaths, including suicides, homicides, homicides followed by suicides, and deaths resulting from child maltreatment or intimate partner violence, as well as legal intervention and accidental firearm deaths. Despite the availability of data from police narratives, medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Based on the NVDRS definition of “homicide‐suicide,” this study was limited to incidents where the homicides occurred within 24 hr of the suicide. Also, there were recent concerns that studying homicide‐suicides in NVDRS is problematic in that the system is believed to misclassify other forms of violence as “homicide‐suicide” (Knoll, ; McNally, Patton, & Fremouw, ). This concern resulted from a misperception that NVDRS does not have a unique code identifying homicide‐suicide cases.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the NVDRS definition of “homicide‐suicide,” this study was limited to incidents where the homicides occurred within 24 hr of the suicide. Also, there were recent concerns that studying homicide‐suicides in NVDRS is problematic in that the system is believed to misclassify other forms of violence as “homicide‐suicide” (Knoll, ; McNally, Patton, & Fremouw, ). This concern resulted from a misperception that NVDRS does not have a unique code identifying homicide‐suicide cases.…”
Section: Methodsmentioning
confidence: 99%
“…Perpetrators of IP homicide-suicide may also have prior interactions with the criminal justice system, and therefore, this setting may provide opportunities for prevention. One study found among 439 defendants of the Bronx Misdemeanor Domestic Violence Court, an estimated 72% of the defendants had prior arrests and 57% had prior assault charges (Puffett & Gavin, 2004).…”
mentioning
confidence: 99%
“…Another issue that arises more generally with murder‐suicides is that they are usually not recorded on databases as such, but tend to be separately recorded as either a suicide or a homicide for each decedent . For example, the lack of a unique code for murder‐suicide, with no linking of cases, or procedure for finding them, has made their identification on the National Violent Death Reporting System (NVDRS) in the United States “problematic” .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, privacy preserving pattern mining [26][27][28] and distributed mining [26] have attracted considerable interests. In health care, SPM has applications in heart disease prediction [29], healthcare auditing [30], and neurological diagnosis [31], violent death reporting [32] etc. The input data to an SPM is a set of sequences, which comprises a list of events ordered by temporal relations.…”
Section: B Spm Background and Related Workmentioning
confidence: 99%